The highly sensitive and facile colorimetric detection of the glycidyl azide polymer based on propargylamine functionalized gold nanoparticles using click chemistry1. Issue 60 (4th August 2015) - He, Yi; Liang, Yun; Wang, Dunju
<x xml:space="preserve">Abstract</x> A highly sensitive and facile colorimetric sensor for the glycidyl azide polymer explosive was developed based on propargylamine functionalized gold nanoparticles using click chemistry.